Telerehabilitation Initiated Early in Post-Stroke Recovery: A Feasibility Study. (February 2023) - Edwards, Dylan; Kumar, Sapna; Brinkman, Lorie; Ferreira, Isabel Cardoso; Esquenazi, Alberto; Nguyen, Tiffany; Su, Michael; Stein, Stephanie; May, Jaun; Hendrix, Allison; Finley, Casey; Howard, Emily; et al.
Background: Enhanced neural plasticity early after stroke suggests the potential to improve outcomes with intensive rehabilitation therapy. Most patients do not get such therapy, however, due to limited access, changing rehabilitation therapy settings, low therapy doses, and poor compliance. Objective: To examine the feasibility, safety, and potential efficacy of an established telerehabilitation (TR) program after stroke initiated during admission to an inpatient rehabilitation facility (IRF) and completed in the patient's home. Methods: Participants with hemiparetic stroke admitted to an IRF received daily TR targeting arm motor function in addition to usual care. Treatment consisted of 36, 70-minute sessions (half supervised by a licensed therapist via videoconference), over a 6-week period, that included functional games, exercise videos, education, and daily assessments. Results: Sixteen participants of 19 allocated completed the intervention (age 61.3 ± 9.4 years; 6 female; baseline Upper Extremity Fugl–Meyer [UEFM] score 35.9 ± 6.4 points, mean ± SD; NIHSS score 4 (3.75, 5.25), median, IQR; intervention commenced 28.3 ± 13.0 days post-stroke). Compliance was 100%, retention 84%, and patient satisfaction 93%; 2 patients developed COVID-19 and continued TR. Post-intervention UEFM improvement was 18.1 ± 10.9 points ( P < .0001); Box and Blocks, 22.4 ± 9.8 blocks ( P = .0001). Digital motor assessments, acquired daily in the home, were concordant with these gains. The dose of rehabilitation therapy received as usual care during this 6-week interval was 33.9 ± 20.3 hours; adding TR more than doubled this to 73.6 ± 21.8 hours ( P < .0001). Patients enrolled in Philadelphia could be treated remotely by therapists in Los Angeles. Conclusions: These results support feasibility, safety, and potential efficacy of providing intense TR therapy early after stroke. Clinical Trial Registration: clinicaltrials.gov; NCT04657770